Clinical efficacy of modified suanzaoren decoction compared to esazolam tablets in the treatment of chronic insomnia disorder - Yao, Ping; Guo, Xingyan; Guo, Zhiguo; Lin, Wuhong; Liu, Min; Chen, Min; Li, Jie; Cui, Long-Biao; Lv, Dongsheng (Frontiers in Psychiatry, 2025)
BackgroundTraditional Chinese medicine is one of the important methods for treating chronic insomnia disorder (CID).AimsWe aimed to observe the multi-dimensional clinical outcomes of modified suanzaoren decoction (SZRD) compared to esazolam tablets in the treatment of CID patients.MethodsA total of 80 patients with CID were divided into two treatment groups, and were given modified SZRD and esazolam tablets treatment respectively for 6 weeks. The Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index, Hamilton Anxiety Scale, Hamilton Depression Scale, polysomnography (PSG), repeated battery for the assessment of neuropsychological status were performed to assess the changes of subjective and objective sleep, mood, and cognitive function.ResultsIntra-group improvement: Compared to before treatment, both the modified SZRD and estazolam groups showed improvements in subjective sleep, depression, anxiety, immediate memory, and delayed memory scores (P<0.05). Inter-group comparison: There was a significant difference between the modified SZRD and estazolam groups in subjective PSQI scores (P=0.033). Based on PSG objective assessment results, both the estazolam and modified SZRD groups demonstrated a significant increase in N3 stage sleep (slow-wave sleep) duration compared to before treatment (P=0.037). However, there was no statistically significant difference in the effect size between the two groups (P>0.05), indicating that both interventions were equivalent in improving deep sleep. Nevertheless, residual variance analysis indicates that estazolam showed enhanced predictive stability in subjective sleep quality assessed by ISI (SSR=11.73 vs. 31.19; F=13.39, P<0.001), while modified SZRD exhibited enhanced predictive stability in objective slow-wave sleep maintenance, specifically in N3 stage duration (SSR=703.11 vs. 1761.08; F=4.98, P=0.029).ConclusionAfter the treatment of CID with the modified SZRD and esazolam, they have the comparable clinical efficacy. However, estazolam showed a more consistent treatment effect in subjective sleep quality assessment among the study population, whereas modified SZRD showed a more consistent treatment effect in objective slow-wave sleep maintenance, specifically in N3 stage duration. The registration number was NCT06452953.